Identifikasi Faktor Penentu Kecurangan Pada UMKM: Perspektif Hexagon Theory Dan Efektivitas Pengendalian Internal - Fitria Suprapto; Fadlil Abdani; Dimas Meireno Jawaahir (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to investigate the factors that can encourage employees to commit fraud in SMEs. The fraud hexagon theory is used to examine the influence of pressure, opportunity, rationalization, capability, arrogance, and collusion on fraudulent acts by employees, with the effectiveness of internal control as a moderating variable. This study uses primary data with a survey approach, so that questionnaires are distributed to respondents as the main data collection tool. From the questionnaires distributed to SME employees in Indonesia, 400 respondents were obtained, with the majority having a bachelor's degree (63.33%) and 5-10 years of work experience (46%) for analysis. The research hypothesis was tested using SEM-PLS. The results of the structural model analysis indicate that not all six components of the fraud hexagon theory drive employees to commit fraud in SMEs. Only the constructs of pressure and capability have a significant influence on employee fraud. Internal control effectiveness can influence the relationship between capability and employees to commit fraud. Without pressure and knowledge, a person cannot create a plan that can prevent fraud from being detected, but mitigation measures can be carried out with the implementation of strict internal controls. This study has implications for SME owners and managers in an effort to maintain SME resilience in the long term so that losses caused by employee fraud can be prevented.